Skin manifestations of connective tissue diseases in childhood. 1. Scleroderma. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
78 cases of connective tissue diseases were observed among 33,250 pediatric dermatoses. Scleroderma is 5 times more frequent than lupus erythematosus and dermatomyositis in children and mainly affects females as well as in adults. The sclerotic changes may involve only a limited part of the skin connective tissue (localized scleroderma), all the skin connective tissue (generalized scleroderma) and the connective tissue of other organs besides the skin (systemic sclerosis). The most frequent clinical forms of scleroderma in children are treated and their pathogenesis is discussed also in the light of the relevant literature.